divide 51x^2y^3z^3/(-85)x^2yz^3 help me i need it fast
Answers
Answered by
0
Answer:
Step-by-step explanation:
(-3x2yz2)3(2y3z3)
Final result :
( -33•2x6y6z9)
Step by step solution :
Step 1 :
Equation at the end of step 1 :
((0-(((3•(x2))•y)•(z2)))3)•(2y3•z3)
Step 2 :
Equation at the end of step 2 :
((0 - ((3x2 • y) • (z2)))3) • 2y3z3
Step 3 :
Multiplying exponential expressions :
3.1 y3 multiplied by y3 = y(3 + 3) = y6
Multiplying exponential expressions :
3.2 z6 multiplied by z3 = z(6 + 3) = z9
Final result :
( -33•2x6y6z9)
Similar questions